ANALISIS MANAJEMEN KEPEMIMPINAN KEPALA MADRASAH DITINJAU DARI DIMENSI KECERDASAN EMOSIONAL - Muslihatuz Zahro' , Finy (UNISAN JURNAL, 2024)
Leadership of a school principal is considered very effective when based on emotional intelligence, bringing positive impacts on the sustainability of the organizational foundation. Therefore, this study seeks to analyze the leadership of school principals from the perspective of emotional intelligence. This research employs a qualitative approach aimed at describing the leadership of school principals and analyzing it through the lens of emotional intelligence. Data collection methods include observation, interviews, and documentation, while data validity is tested using triangulation techniques, particularly source triangulation. The sources of data encompass the entire school community, the surrounding environment, and individuals interacting with the principal, including teachers. This information is used to depict the principal’s leadership based on emotional intelligence. The findings reveal that the analyzed principal demonstrates excellent leadership when viewed from the perspective of emotional intelligence. Further analysis indicates that the principal effectively implements primal leadership, as evidenced by data and source triangulation. The principal shows a strong commitment to the school’s vision for the future, especially during challenging times or periods of increased responsibility. Additionally, the principal possesses strong self-awareness and self-management, high social awareness, and effective relationship management skills.